Management of Human Impacts on the Natural Environment at Devil’s Lake State Park, WI - Heilig, Brian; Peterson, Jacob Lu; Lemke, Nikolas (My University, 2019)
The presented paper explores: How do Parks, specifically Devil’s Lake State Park, balance visitor impacts with conservation goals, to mitigate prevalent environmental consequences from visitor activities/presence? Under the DNR missions we looked to see how successful those goals of trying (1) to conserve natural and cultural sites, and (2) facilitating recreational use through hiking, biking, sightseeing, swimming, and other activities caused from high rates of overcrowding. The primary research method was an interview the superintendent of Devil’s Lake State Park Steve Schmelzer combined with a literature review. The most important issues to the park are those around hiking camping and overcrowding. Hiking is the most popular activity, camping the most infrastructure intensive, and overcrowding exacerbates any issues with hiking, camping, and other activities. While dealing with these issues, the Department of Natural Resources and Devil’s Lake State Park refuse to discourage people from enjoying the park. Instead they focus on mitigating the marginal impact of each visitor while encouraging them to explore the state park system.
Includes Photographs, Maps, Graphs, Appendices and Bibliography.
Keywords: Devil's Lake State Park; Natural environment; Human impacts